Information System Design Of Production Data Processing Company Mechanical Manufacturing - Hurnaningsih Hurnaningsih; Elly Agustina Julisawati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Before making changes to the data processing process on the existing data processing system, PT. XYZ already uses an application to manage production data. The current system is no longer able to support existing operations so that data processing is carried out using Microsoft Excel. Based on an interview with one of the employees of the production division, it is known that data processing using Microsoft Excel is not ideal for helping employees' tasks. As in the process of entering data, employees feel tired because they enter so much data into the Microsoft Excel application which causes frequent errors. The data file is only stored on one of the production employees' computers so that it does not allow other production employees to access the data which slows down the data entry process and makes it difficult to generate production data reports. The development of a web-based production data processing application is a suggested solution based on the current problems. This application was developed with the employee's permission on a web platform because employees can use and access it more easily via the internet (web). Production data processing application that will be made at PT. XYZ can solve current problems and help and improve staff performance in carrying out their work.